A Politico-Economic Model of Aging, Technology Adoption and Growth - Giovanni Prarolo; Francesco Lancia (Fondazione Eni Enrico Mattei (FEEM), 2007)
Over the past century, all OECD countries have been characterized by a dramatic increase in economic conditions, life expectancy and educational attainment. This paper provides a positive theory that explains how an economy might evolve when the longevity of its citizens both influences and is influenced by the process of economic development. We propose a three periods OLG model where agents, during their lifetime, cover different economic roles characterized by different incentive schemes and time horizon. Agents decisions embrace two dimensions: the private choice about education and the public one upon innovation policy. The theory focuses on the crucial role played by heterogeneous interests in determining innovation policies, which are one of the keys to the growth process: the economy can be discontinuously innovation-oriented due to the different incentives of individuals and different schemes of political aggregation of preferences. The model produces multiple development regimes associated with different predictions about life expectancy evolution, educational investment dynamics, and technology adoption policies. Transitions between these regimes depend on initial conditions and parameter values.
Keywords: D70; J10; O14; O31; O43; 330; Growth; Life Expectancy; Human Capital; Systemic Innovation; Majority Voting; Sterblichkeit; Humankapital; Alternde Bevölkerung; Overlapping Generations; Innovationspolitik; Theorie; OECD-Staaten